Cybertexts and hypertexts: literature in the digital era - Verônica Daniel Kobs (Cadernos de Letras da UFF, 2017)
Based mainly on Lucia Santaella, Winfried Nöth and Luis Arata’s studies, this article analyzes the changes happened in the literature, for the use of the electronic support in the creation and reading of literary texts. Thus, some cybertexts will be analyzed, to exemplify the function of the movement in the digital Literature. Besides, hypertexts will be presented, to emphasize the several options of interaction and reading. ---   DOI: http://dx.doi.org/10.22409/cadletrasuff.2017n54a381